ASSESSMENT OF A ONE-WAY POLICY IN A MAJOR ROAD: THE CASE OF QUEZON AVENUE IN VIGAN CITY, ILOCOS SUR - Amistad, Franklyn T. (Philippine Engineering Journal; Vol 33 No 2 (2012), 2013)
This study focused on the assessment of a one-way policy in a major road in the City of Vigan Philippines. It aimed to characterize the area, pedestrians and level of service of intersections; analyze the perceptions of respondents on the necessity, acceptability and impact of the one-way scheme and test the relationships between perceptions and attributes of the respondents. It is recommended that the city government of Vigan should enact a “No loading” policy and minimal time for unloading of passengers and a “Give way to Pedestrians” policy for maximum safety. It is suggested that the traffic enforcers should strictly implement traffic rules, laws, and regulations found in the Land Transportation and Traffic Code of the Philippines. The City government should adopt some environmentally sustainable transport strategies in the pursuit of a sustainable development of the city of Vigan without sacrificing its legacy as a world heritage site. Keywords: Major Road, Traffic Management, Environmentally Sustainable Transport